High prevalence of hepatitis B and poor knowledge on hepatitis B and C viral infections among barbers: a cross-sectional study of the Obuasi municipality, Ghana - Adoba, Prince (BMC Public Health, 2015)
BACKGROUND: Barbers, while shaving, may be accidentally exposed to the blood and bodily fluids of their customers increasing their risk of contraction of HBV and HCV infections. Hence, this study aimed at examining the prevalence and knowledge of barbers on HBV and HCV infections in the Obuasi municipality of Ghana. METHODS: A work place based cross-sectional study was conducted from January to April 2015 at the Obuasi municipality in the Ashanti Region of Ghana. Two hundred (200) barbers were conveniently recruited and blood sample of each participant collected for the detection of HBsAg and HCV antibodies. Data on socio demographic characteristics, and knowledge on HBV and HCV infections were collected using a structured and pre-tested questionnaire. Analysis was performed using SPSS version 16.0, and P < 0.05 was considered statistically significant. RESULTS: The prevalence of HBV and HCV among the barbers were 14.5 % and 0.5 % respectively. HBV was highest among barbers within 20–29 years (58.6 %). Majority (90.5 %) of the participants had heard of HBV infection before. The mode of transmission of HBV was unknown by 64.5 % of the participants and 64.0 % did not perceive themselves to be at risk for HBV. Most of the participants had never heard of HCV infection (61.3 %), and unaware of any mode of transmission of HCV (97.0 %). The radio was the major source of information on HBV (57.5 %) and HCV (25.0 %) infections. CONCLUSION: High prevalence of HBV and low knowledge on HBV and HCV infections was found among barbers. Barbers need to be educated on viral hepatitis to reduce the acquisition of HBV and HCV infections.